Pengaruh Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, dan Pengangguran terhadap Tingkat Kemiskinan Kabupaten/Kota di Provinsi Sumatera Utara Tahun 2017-2021 - Regista Klaudia Kaban; Mulyo Hendarto Robertus (Diponegoro Journal of Economics, 2023)
One of the obstacles in the development of developing countries including Indonesia is poverty or the number of people below the poverty line. In an effort to reduce poverty, research is needed on the factors that influence poverty between regions. The purpose of this study is to analyze the effect of Gross Regional Domestic Product (GRDP), Human Development Index (HDI) and Unemployment on Poverty levels in 33 District/Cities in North Sumatera Province in 2017-2021. This study uses panel data with the Random Effect Model (REM) approach and uses a one-tail hypothesis test to determine the effect of Gross Regional Domestic Product (GRDP), Human Development Index (HDI) and Unemployment on District/City Poverty Levels in North Sumatera Province in 2017-2021. The regression results using the Random Effect Model (REM) approach show that partially, the Gross Regional Domestic Product (GRDP) and Human Development Index (HDI) variables have a significant effect on the district/city poverty rate in North Sumatera Province, while the unemployment variable has no significant effect on the district/city poverty rate in North Sumatera Province. Suggestions for this study are to add other independent variables that are not included in this research model, in addition to what factors affect the poverty rate.